2020
DOI: 10.12737/1024-6177-2020-65-1-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Treatment of Radiation Skin Lesions with Mesenchymal Stem Cells and Their Conditioned Media

Abstract: Purpose: To study the regeneration processes in the treatment of radiation skin lesions with the mesenchymal stem cells (MSC) derived from human gingiva and their conditional medium concentrate (CCM) during animal studies. Material and methods: The study includes 80 white male Wistar rats weighing 210 ± 30 g at the age of 8–12 weeks, randomized into 4 groups (20 animals in each): control group (C), animal did not receive treatment; control with the introduction of the conditional medium concentrate (CCM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In our previous study [7], the effectiveness of the use of MSCs of the gingival mucosa in LRI was shown. The absence of a significant effect when using MSCs derived from the placenta in this study is due to the tissue specificity of this cell source and the peculiarities of their production of paracrine factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our previous study [7], the effectiveness of the use of MSCs of the gingival mucosa in LRI was shown. The absence of a significant effect when using MSCs derived from the placenta in this study is due to the tissue specificity of this cell source and the peculiarities of their production of paracrine factors.…”
Section: Discussionmentioning
confidence: 98%
“…Radiation to human skin in doses exceeding 8 Gy may lead to the development of local radiation injuries (LRI) [4]. In radiotherapy of oncological diseases, LRI is registered in 20-40% of cases [7]. Skin LRIs are characterized by the development of recurrent ulcers with pain syndrome, which significantly lengthens the treatment process due to persistent damage to blood and lymphatic vessels with the progression of tissue fibrosis, which worsens the results of treatment and the quality-of-life of patients [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation